2021
DOI: 10.1186/s12890-021-01408-7
|View full text |Cite
|
Sign up to set email alerts
|

SPAK-p38 MAPK signal pathway modulates claudin-18 and barrier function of alveolar epithelium after hyperoxic exposure

Abstract: Background Hyperoxia downregulates the tight junction (TJ) proteins of the alveolar epithelium and leads to barrier dysfunction. Previous study has showed that STE20/SPS1-related proline/alanine-rich kinase (SPAK) interferes with the intestinal barrier function in mice. The aim of the present study is to explore the association between SPAK and barrier function in the alveolar epithelium after hyperoxic exposure. Methods Hyperoxic acute lung injury… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The underlying mechanisms in which ischemic stroke triggers activation of SPAK–NKCC1 complex in ChP remains undefined. It was reported that ROS stimulate SPAK phosphorylation and causes Claudin-18 disruption in alveolar epithelium cell following hyperoxia insult [ 44 ]. To determine whether the ROS-mediated mechanism upregulates SPAK–NKCC1 cascade phosphorylation activity in the ChP, we established an in vitro model of primary cultures of CPECs which expressed abundant epithelial cell cytoskeletal protein cytokeratin as well as TJ ZO-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanisms in which ischemic stroke triggers activation of SPAK–NKCC1 complex in ChP remains undefined. It was reported that ROS stimulate SPAK phosphorylation and causes Claudin-18 disruption in alveolar epithelium cell following hyperoxia insult [ 44 ]. To determine whether the ROS-mediated mechanism upregulates SPAK–NKCC1 cascade phosphorylation activity in the ChP, we established an in vitro model of primary cultures of CPECs which expressed abundant epithelial cell cytoskeletal protein cytokeratin as well as TJ ZO-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying cellular and molecular mechanisms are not completely understood. A recent study shows that ROS-mediated upregulation of pSPAK in alveolar epithelium cells is linked to loss of TJ Claudin-18 protein, knockdown of SPAK preserved the alveolar epithelium barrier integrity after hyperoxic stress [ 44 ]. Moreover, manganese, oxidants and NO donors have been reported to increase the oxidation and nitration of NKCC1 protein and upregulation of total and phosphorylated NKCC1 protein expression in cultured astrocytes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that carbonic anhydrase 9 (CAIX), phorbol 12-myristate 13-acetate (PMA), c-jun, epidermal growth factor (EGF) and RAS can upregulate the expression of CLDN18 (15,(55)(56)(57) and that interleukin-1b (IL-1b), hyperoxia, STE20/ SPS1-related proline/alanine-rich kinase (SPAK) can inhibit CLDN18 expression (57,58). The possible mechanisms are summarised as follows:…”
Section: Regulation Of Cldn18 Expressionmentioning
confidence: 99%
“…Patients with corticosteroid-resistant asthma demonstrate airway expansion of specific Gram-negative bacteria, which trigger MYD88-dependent transforming growth factor-β-associated kinase-1 activation, resulting in p38 MAPK phosphorylation, NF-κB activation, and transcription of pro-inflammatory cytokines [172]. Repeated exposure to LPS has been shown to activate PI3K, resulting Lung injury models: LPS-, peritonitis-, thrombin-, and LPS-and ventilation-induced injury in mice and rats, and primary rat and human pulmonary microvascular endothelial cells, A549 cells, human umbilical vein endothelial cells (HUVEC), alveolar epithelial cells, MLE-12 cells, primary rat alveolar type II epithelial cells, human pulmonary artery endothelial cells, human small airway epithelial cells [193 194 195-211] Decrease in occludin, claudin-3, claudin-4, claudin-5, claudin-7, and claudin-18, ZO-1, and E-cadherin; increase in claudin-4; no change in claudin-4 and claudin-5; and altered distribution and localization of E-cadherin Ventilation-induced lung injury or hyperoxia: Hyperoxia-, stretch-, and ventilation-induced injury in mice and rats, and primary rat lung epithelial cells, primary rat alveolar epithelial cells, primary neonatal rat alveolar epithelial cells, rat lung slices, MLE-12 cells [51,63,[212][213][214][215][216] Decrease in claudin-5 and claudin-18, and occludin; altered distribution of claudin-5 and claudin-18, and occludin; altered JAM-A Bleomycin-and TGF-β-induced lung injury in mice, and A549 cells, HUVEC cells, and E10 immortalized lung epithelial cell line [217,218] Decrease in claudin-3 and claudin-18, ZO-1, occludin, and JAM-A; increase in occludin and dephosphorylated connexin-43…”
Section: Role Of Tlr4 In Resistance To Corticosteroid Treatmentmentioning
confidence: 99%